Efeito dos imunoestimulantes levamisol e glicano nas respostas fisiológicas e no desempenho de juvenis de tambaqui, Colossoma macropomum, (Cuvier, 1817) sob condições de cultivo e transporte - Silva, Ana Maria Dias da (Instituto Nacional de Pesquisas da Amazônia - INPA, 2011)
Three studies were held to evaluate levamisol and glucan in diet to improve juvenile tambaqui growth and stress mitigate effect. In the first experiment (Chapter 2), it was determined juvenile tambaqui tolerance to Aeromonas hydrophila (96h-LD50) that ranged in 2,4 x 1011 UFC A. hydrophila mL-1 of saline solution. In the third chapter of this thesis, it was evaluated levamisole and glucan in diet effect on growth and juvenile tambaqui physiological, metabolic and immunological responses to 60% of 96h-LD50 A. hydrophila. The results allowed establishing levamisole and glucan in diet did not interfere on growth and feed conversion rates. Glucan and levamisole did not alter lisozyme activity but they stimulated part of non-specific immune system of juvenile tambaqui. However, they were unable to minimize to artificial bacteria infection. The best results were obtained with levamisole in concentration of 250 and glucan 5mg. In chapter 4, it was evaluated these two (250 and 5 mg) levamisole and glucan concentrations in diets given to juvenile tambaqui stocked in cages during 60 days. It was also evaluated growth and physiological stress responses of fish after transport. The results showed levamisole and glucan were not able to interfere on growth parameters. It was observed alterations on blood, biochemical and immunological parameters immediately after transport and fish recovery after 24 h. Levamisole and glucan could not minimize stress responses.
Keywords: Colossoma macropomum; Tambaqui; Imunoestimulante; Aquicultura